Successful anesthetic management of a child with blepharophimosis syndrome and atrial septal defect for reconstructive ocular surgery - Dalim Kumar Baidya; Puneet Khanna; Anil Kumar; Dilip Shende (Wolters Kluwer Medknow Publications, 2011)
Blepharophimosis syndrome is an autosomal dominant disorder characterized by eyelid malformation, involvement of reproductive system and abnormal facial morphology leading to difficult airway. We report a rare association of blepharophimosis syndrome and atrial septal defect in a 10-year-old girl who came for reconstruction surgery of eyelid. The child had dyspnea on exertion. Atrial septal defect was identified preoperatively by clinical examination and echocardiography. Anesthesia management was complicated by failure in laryngeal mask airway placement and Cobra perilaryngeal airway was subsequently used.